(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to investigate the concept of character education values at the Modern Islamic Boarding School Darussalam Gontor Putri Campus 1, analyze its implementation in the Annual Introduction Week of Khutbatul ’Arsy, identify supporting and inhibiting factors, and determine its influence on female students. The method used is descriptive qualitative research, with data collection techniques through interviews, observations, and documentation. Data analysis adopts the Miles and Huberman model, including data reduction, data presentation, and verification. The results of the study indicate that the concept of character education values at Gontor Putri Campus 1 is the main foundation for changing the personality of female students, prioritized over teaching science, and integrated into all aspects of the boarding school life for 24 hours. The implementation of character values such as sincerity, patience, gratitude, responsibility, totality, self-reflection, sincerity, honesty, and love for the country is carried out through various programs and series of Khutbatul ’ArArsy events. The main supporting factors include leadership as a role model and the enthusiasm of female students, while inhibiting factors such as the large number of female students and lack of understanding are overcome with in-depth guidance and direction. The implementation of these values significantly influences female students by broadening their insight into Gontor’s philosophy, providing extensive life experiences and provisions, and forming individuals with strong characters. In conclusion, the Annual Introduction Week of Khutbatul ’Arsy has proven to be an effective medium in fostering character education, deeply instilling Gontor’s core values, and preparing female students to play an active role in society.